Genetic diversity and multidrug-resistance among Salmonella Typhimurium isolated from swine carcasses and slaughterhouses in Rio de Janeiro, Brazil - Cabral, Claudius; Panzenhagen, Pedro; Frensel, Karina; Rodrigues, Gabriela; Mercês, André; Rodrigues, Dalia; Franco, Robson; Conte-Junior, Carlos Adam (Veterinaria Italiana, 2020)
This study, conducted in the State of Rio de Janeiro, aimed to genetically distinguish 29 isolates of S. Typhimurium isolated from 344 samples of swine carcasses by PFGE (pulse‑field gel electrophoresis) and to evaluate their antimicrobial resistance profile. Out of the 29 isolates, 26 (90%) were resistant to at least one antimicrobial. Sulfonamides (66%), nalidixic acid (66%), trimethoprim (66%) and tetracycline (52%) were the most frequent resistant drugs. Multidrug‑resistance (MDR) profile was frequent (60% of isolates). The profile Eno‑Na‑Nxn‑Fc‑C‑S‑Gm‑G‑T‑Te (14%), Cp‑Eno‑Na‑Fc‑C‑S‑G‑T‑Te (10%) and Na‑G‑T (7%) were the most frequent. Five isolates within the predominant PFGE pulsetype came from lymph nodes of distinct animals from multiple slaughterhouses indicating that this particular clone might be widespread in the Rio de Janeiro State. This paper reveals a threat to the population in the entire State and highlights the necessity of the strict control in the use of antimicrobials in swine production in the entire country.